Factors influencing the public's decision-making to undergo health checks for prevention of cardiovascular disease / Cheong Ai Theng - Cheong, Ai Theng (2017)
Cardiovascular disease (CVD) is the leading cause of mortality globally and in Malaysia. The prevalence of cardiovascular risk factors is high in this country, and more than half of those with risk factors remain ignorant of their cardiovascular risk status. Thus, there is a need to improve the public’s participation in health checks for early identification of individuals at high risk for CVD prevention. Early identification will enable measures to be taken to prevent CVD morbidity and mortality. The purpose of this study was to explore the determinants and process of decision-making by the public with regard to health check participation for CVD prevention, and then identify possible factors to target the development of effective strategies to improve CVD health check participation. This study was conducted in three phases. In phase I, a systematic review was conducted to determine the effectiveness of existing intervention strategies to increase the uptake of cardiovascular risk factor screening. This was followed by a sequential exploratory mixed-method in phase II and phase III. In phase II, a qualitative study was carried out using a grounded theory approach to develop an explanatory framework for an individual’s decision-making process for participation in CVD health checks. This framework was then used in the conceptualization and development of an instrument in phase III, in which a cross-sectional survey was carried out to identify the significant determinants associated with the public’s intention to undergo CVD health checks. A systematic review of the literature showed that effective intervention in promoting uptake of cardiovascular risk factor screening included physician reminders, using dedicated personnel and providing financial incentives to individuals. Nevertheless, there was high heterogeneity for the meta-analysis performed. At the individual level, the decision to undergo CVD health checks was multi-factorial. The main factor was an individual’s intention to undergo health checks, which was a result of two key internal iv factors: the perception of relevance and the state of readiness to act on or cope with the findings of the health checks. The intention of the health checks is subsequently modified by external factors such as influences from significant others, as well as time, cost, accessibility and health care facilities. At the population level, four significant determinants were found to be associated with the intention to undergo CVD health checks: the perception of benefits and drawbacks of CVD health checks, the perception of external barriers and the readiness to handle outcomes following CVD health checks. Overall, although interventions studied in the systematic review targeted mainly external factors, results from phase II and III noted internal factors appeared to be more important than external factors. This research highlights the need for interventions to improve health check participation to focus on internal factors and not simply target external factors. In conclusion, the study has provided an understanding of the factors influencing the public’s decision to undergo CVD health checks from both individual and general public perspectives. These factors can thus be incorporated in developing interventions using effective evidence-based strategies for cardiovascular risk factor screening.